Anti-inflammatory effects of three selenium-enriched brown rice protein hydrolysates in LPS-induced RAW264.7 macrophages via NF-κB/MAPKs signaling pathways. (January 2021) - Feng, Mingju; Wang, Xiaoya; Xiong, Hua; Qiu, Tingting; Zhang, Hua; Guo, Fanghua; Jiang, Li; Sun, Yong
Graphical abstract: The anti-inflammatory mechanism of peptide fractions. Highlights: Three Se-enriched brown rice protein hydrolysates were prepared. The anti-inflammatory property of protein hydrolysates was investigated. The relationship between anti-inflammatory property and molecular weight. Abstract: In the present study, three selenium-enriched brown rice protein hydrolysates were prepared by trypsin, their anti-inflammatory mechanism in vitro were investigated. Results obtained from LPS-induced RAW264.7 cell model showed that the 1.0–3.5 kDa peptide fractions exhibited the most effective anti-inflammatory property through inhibiting the production of nitric oxide (NO), prostaglandin E2 (PGE2 ) and pro-inflammation cytokines including interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α). The mRNA and protein expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) were also suppressed by 1.0–3.5 kDa peptide fractions. Additionally, the phosphorylation of nuclear factor-κB (NF-κB) and mitogen-activated protein kinases (MAPKs) signal proteins were blocked after 1.0–3.5 kDa peptide fraction treatments. Above all, the observed anti-inflammatory effects of selenium-enriched brown rice protein hydrolysates were closely related to their Se content. These results illustrated that the 1.0–3.5 kDa peptide fractions could be a novel functional food ingredient for inflammation-related diseases treatment.